Similarities and differences in child development from birth to age 3 years by sex and across four countries: a cross-sectional, observational study - Ilgi Ozturk Ertem, ProfMD; Vibha Krishnamurthy, MD; Mphelekedzeni C Mulaudzi, MD; Yanina Sguassero, MD; Hakan Balta, MD; Ozlem Gulumser, MD; Burcu Bilik, MSc; Roopa Srinivasan, MD; Benjamin Johnson, MSc; Geliang Gan, PhD; Lisa Calvocoressi, PhD; Veronika Shabanova, PhD; et al. (Elsevier, 2018)
Summary: Background: Knowledge about typical development is of fundamental importance for understanding and promoting child health and development. We aimed to ascertain when healthy children in four culturally and linguistically different countries attain developmental milestones and to identify similarities and differences across sexes and countries. Methods: In this cross-sectional, observational study, we recruited children aged 0-42 months and their caregivers between March 3, 2011, and May 18, 2015, at 22 health clinics in Argentina, India, South Africa, and Turkey. We obtained a healthy subsample, which excluded children with a low birthweight, perinatal complications, chronic illness, undernutrition, or anaemia, and children with missing health data. Using the Guide for Monitoring Child Development, caregivers described their child's development in seven domains: expressive and receptive language, gross and fine motor, play, relating, and self-help. Clinicians examining the children also completed a checklist about the child's health status. We used logit and probit regression models based on the lowest deviance information criterion to generate Bayesian point estimates and 95% credible intervals for the 50th percentile ages of attainment of 106 milestones. We assessed the significance of differences between sexes and countries using predefined criteria and regions of practical equivalence. Findings: Of 10 246 children recruited, 4949 children (48·3%) were included in the healthy subsample. For the 106 milestones assessed, the median age of attainment was equivalent for 102 (96%) milestones across sexes and 81 (76%) milestones across the four countries. Across countries, median ages of attainment were equivalent for all play milestones, 20 (77%) of 26 expressive language milestones, ten (67%) of 15 receptive language milestones, nine (82%) of 11 fine motor milestones, 14 (88%) of 16 gross motor milestones, and eight (73%) of 11 relating milestones. However, across the four countries the median age of attainment was equivalent for only two (22%) of nine milestones in the self-help domain. Interpretation: The ages of attainment of developmental milestones in healthy children, and the similarities and differences across sexes and country samples might aid the development of international tools to guide policy, service delivery, and intervention research, particularly in low-income and middle-income countries. Funding: Eunice Kennedy Shriver National Institute of Child Health and Human Development.